Infectious bronchitis associated with Escherichia coli infection in commercial broiler chickens: a case report (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: In this case report, we have investigated the infectious bronchitis (IB) virus (IBV) outbreak with the co-infection of Escherichia coli in 28–33-day-old broiler chickens in Malaysia.  Materials and Methods: A farmer complained that Cobb 500 chickens, raised in the open house, were having bloody diarrhea, open mouth breathing, non-uniform growth, and ruffled feathers. The mortality was about 100 birds (from about 7000 birds) per day. The sick birds were isolated and subjected to physical examination, postmortem, and histopathological analyses. Gross lesions were observed and recorded. The lung samples have proceeded with histopathological evaluations. The lungs, kidneys, trachea, air sac, and heart samples were collected to isolate bacteria and fungi through a series of conventional cultural methods, followed by molecular confirmation of the IBV.  Results: Postmortem examination revealed air sacculitis, hemorrhagic tracheitis, pulmonary congestion, fibrin deposition in the liver and air sac, hemorrhagic enteritis, and renomegaly. The bacterial culture and biochemical tests revealed E. coli in the lungs, trachea, liver, intestine, and kidney samples. However, no fungus could be isolated from those samples. Histological evaluation of lung samples demonstrated infiltration of inflammatory cells in the pulmonary tissues. Apart from this, reverse transcription-polymerase chain reaction confirmed the presence of avian coronavirus responsible for infectious bronchitis (IB).  Conclusion: The chickens were diagnosed with IB concurrent with E.coli. The chickens exhibited typical nephropathogenic strain of IBV infection, causing high mortality.J. Adv. Vet. Anim. Res., 8(1): 101-104, Mar 2021http://doi.org/10.5455/javar.2021.h491